Effect of twin pregnancy chorionic properties on maternal and fetal outcomes - Bibo Feng; Jianjun Zhai; Yu Cai (Elsevier, 2018)
Objective: This study aimed to determine the effect of twin pregnancy chorionic properties on pregnancy complications and fetal outcomes. Materials and methods: A total of 559 subjects with gemellary pregnancy were included in the retrospective analysis, and clinical data, such as monitoring data during pregnancy and maternal and fetal outcomes, were recorded in detail. Based on the ultrasound results and methods of the postpartum pathologic examination of the placental membranes, the subjects were divided into the twin group with monochorionic diamnion (MCDA group, n = 198) and twin group with dichorionic diamnion (DCDA group, n = 361). The relationships of different chorionic properties and maternal and fetal outcomes were determined by comparing the maternal complications and fetal outcomes. Results: The occurrence rate of gemellary pregnancy was 2.97% and that of monochorionic twin pregnancy was 34.8%. The MCDA group showed a higher incidence of pregnancy-induced hypertension, gestational diabetes mellitus, polyhydramnios, premature rupture of membranes, and abruptio placenta and a lower incidence of severe postpartum hemorrhage than the DCDA group. However, the incidence of preterm birth was significantly different (57.6% vs. 45.7%, P < 0.05). Significant differences were also detected in the incidence of fetal loss, complicated twins, neonatal asphyxia, and perinatal death between the two groups (P < 0.05). Conclusion: The incidence of maternal complication (such as pregnancy-induced hypertension, gestational diabetes mellitus, polyhydramnios, premature rupture of membranes, and abruptio placenta and severe postpartum hemorrhage) in the two groups was not significantly different; however, the fetal outcomes in the MCDA group were inferior to those in the DCDA group. The fetal outcomes may be improved by determining the chorionic properties in early pregnancy by using ultrasound and consequently planning for pregnancy monitoring and intervention.